ANALISIS KEBUTUHAN BAHAN AJAR MAHARAH KITABAH SISWI KELAS VIII SMP AL-QUR’AN - Nufus, Zahrotun; Amiruddin; Koderi; Erlina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The Arabic textbooks used by teachers and students have too high a language and are difficult for students to understand. The material on the aspect of writing skills is very limited, which has an impact on the lack of students' ability in learning writing skills. The purpose of this study is to analyze the needs of student teaching materials on learning writing skills. The research method used is a qualitative descriptive method that produces research data sourced from needs analysis questionnaires. In the needs analysis that has been carries out, the results obtained that teachers and students need a companion book for learning writing skills as a support in understanding the material presented. So, the learning process will be more focused and students can understand the material well.